Floristic Diversity of Woody Perennials in Katola Range of Mandi forest Division (H.P.) - Rattan, Vidya; Singh, Ombir (Indian Forester, 2009)
The floristic diversity of woody perennials was studied in Katola range of Mandi forest division in Himachal Pradesh. A total of 17 floral families contribute to the 27 species with 62.96% and 37.04% for tree and shrub species respectively. The dominant and co-dominant tree and shrub species was Pinus roxburghii, Quercus leucotrichophora and Berberies aristata, Prinsepia utilis, respectively. Distribution pattern of various tree species was contiguous except Cedrus deodara, P. roxburghii and Myrica esculenta which were random while distribution pattern of shrub species was contiguous except B. aristata. Such site-specific database is imperative as it can potentially provide fundamental information on the species organization, spatial heterogeneity, biotic and abiotic impacts on dynamics of regeneration and growth.